Peritumoral Hyperplasia in Hepatic Sclerosed Hemangioma. Issue 1 (2017) - Shimada, Seitarou; Tajiri, Kazuto; Baba, Hayato; Minemura, Masami; Tsuneyama, Koichi; Nakano, Masayuki; Sugiyama, Toshiro
ABSTRACT : N/A: Peritumoral hyperplasia (PTH) is a hyperplastic lesion located around hypervascular tumors. Hepatic sclerosed hemangioma is a very rare form of hemangioma with sclerotic changes and is distinct from sclerosing hemangioma. We present a patient with non‐alcoholic steatohepatitis‐induced cirrhosis who presented with a hypervascular tumor. The tumor showed atypical findings of hemangioma and was treated with surgical resection because hepatic malignancy could not be ruled out. Histopathologic examination revealed the tumor was a sclerosed hemangioma with PTH. Lesions with carcinogenic potential were found in the PTH lesion. Sclerosed hemangioma should be observed and managed carefully.